Factors Influencing Professional Help-Seeking Behavior During First Episode Psychosis in Schizophrenia: An Exploratory Study on Caregivers’ Perspective - Wong, Daniel Teck Lung; Tong, Seng Fah; Daud, Tuti Iryani Mohd; Aziz, Salina Abdul; Midin, Marhani (Frontiers in Psychiatry, 2020)
Schizophrenia is a severe mental illness that leads to significant productivity loss and is listed in the top 15 global burdens of disease. One important contributor to the high disease burden is duration of untreated psychosis (DUP) which can be shortened with promotion of professional help-seeking behaviour. This study explored caregivers’ perspective on factors influencing professional help-seeking behaviour during first episode psychosis (FEP) in schizophrenia in Malaysia. The results of this study would inform the development of intervention strategies targeted at promoting professional help-seeking behaviour in caregivers of individuals experiencing first episode psychosis (FEP). This is a thematic exploratory study which employed purposive sampling using focus group discussion (FGD). These interviews were audio recorded and transcribed verbatim. Basic thematic approach was used in analysing the transcribed interviews. Two main themes identified were adequacy of knowledge and stigma. These two factors were found to co-influence each other. Stigma undermined the impact of knowledge on professional help-seeking; likewise, the reverse was also observed. Intervention strategies for promoting help-seeking behaviour during FEP should simultaneously focus on improving knowledge about schizophrenia and reducing the stigma attached to it.